Guidelines for process safety documentation. (Center for Chemical Process Safety of the American Institute of Chemical Engineers, 1995)
The process industry has developed integrated process safety management programs to reduce or eliminate incidents and major consequences, such as injury, loss of life, property damage, environmental harm, and business interruption. Good documentation practices are a crucial part of retaining past knowledge and experience, and avoiding relearning old lessons. Following an introduction, which offers examples of how proper documentation might have prevented major explosions and serious incidents, the 21 sections in this book clearly present aims, goals, and methodology in all areas of documentati.
Keywords: Chemical engineering -- Safety measures.; elektronické knihy; electronic books